Job Retention and Career Advancement: A Survey of Persons who are Blind or Have Low Vision. - Crudden, Adele; Carter Steverson, Anne (Journal of Rehabilitation)
A national survey investigated job retention and career advancement among 388 persons with blindness or low vision and employment experience. Most participants received state vocational rehabilitation (VR) agency services and were employed. Employed participants reported that assistive technology was the most helpful VR service. Most were satisfied with their jobs but were interested in career advancement. Employed participants were likely to have positive experiences changing jobs. People who lost vision while employed had difficulty retaining the same level of efficiency and ability to perform their job duties. Slightly over half of unemployed persons said it was not their choice to stop working.